The Lutheran Confessions : History and Theology of The Book of Concord - Arand, Charles P. (Book collections on Project MUSE., 2012)
"From their formulation in the sixteenth century through the present day, every generation of Lutheran leadership has grappled with the centrality and importance of the Lutheran confessional writings. In this important new volume, Arand, Kolb, and Nestingen bring the fruit of an entire generation of scholarship to bear on these documents, making it an essential and up-to-date class text. The Lutheran Confessions places the documents solidly within their political, social, ecclesiastical, and theological contexts, relating them to the world in which they took place, and assists readers in understanding the issues at stake in the narratives, both in their own time and in ours"--Publisher description